Comparison of three different wastewater sludge and their respective drying processes: Solar, thermal and reed beds – Impact on organic matter characteristics. (1st December 2017) - Collard, Marie; Teychené, Benoit; Lemée, Laurent
Abstract: Drying process aims at minimising the volume of wastewater sludge (WWS) before disposal, however it can impact sludge characteristics. Due to its high content in organic matter (OM) and lipids, sludge are mainly valorised by land farming but can also be considered as a feedstock for biodiesel production. As sludge composition is a major parameter for the choice of disposal techniques, the objective of this study was to determine the influence of the drying process. To reach this goal, three sludges obtained from solar, reed beds and thermal drying processes were investigated at the global and molecular scales. Before the drying step the sludges presented similar physico-chemical (OM content, elemental analysis, pH, infrared spectra) characteristics and lipid contents. A strong influence of the drying process on lipids and humic-like substances contents was observed through OM fractionation. Thermochemolysis-GCMS of raw sludge and lipids revealed similar molecular content mainly constituted with steroids and fatty acids. Molecular changes were noticeable for thermal drying through differences in branched to linear fatty acids ratio. Finally the thermal drying induced a weakening of OM whereas the solar drying led to a complexification. These findings show that smooth drying processes such as solar or reed-beds are preferable for amendment production whereas thermal process leads to pellets with a high lipid content which could be considered for fuel production. Graphical abstract: Highlights: Sewage sludge from solar, reed beds and thermal drying processes were compared. Raw wastewater sludge were characterised at the global scale. The organic matter was fractionated into lipids and humic substances. Lipids and raw sludge were analysed by thermochemolysis-GCMS. Thermal and solar drying induced weakening or complexification of the organic matter.